Embedding Business Ethics in Islamic Economic Jurisprudence: A Catalyst for Sustainable Islamic Banking - Kharisma Bening; Wahyu Hamdani (Walisongo Journal of Sharia Economic Law, 2026)
The impact of integrating business ethics into Islamic economics systems' jurisprudence has been a major contributing factor to the continuing viability of Islamic banking institutions. This study examines the global contextual necessity for the integration of Sharia law-based ethics into the operational systems of Islamic financial institutions due to the global scrutiny of ethical banking. This research examines the extent to which Islamic banking is able to gain and/or retain enduring business credibility, resilience, and/or sustainability through the integration of business ethics. This research employs a qualitative research design through the use of doctrinal primary Islamic legal research, supplemented by a review of situational case studies, as well as, regulatory documents of select Islamic financial markets. This research reveals adherence to ethical principles of justice, transparency, social accountability, etc., while supporting the internal Sharia compliance of the institution, enhances stakeholder trust and social Sharia compliance, as well as, the institution's socioeconomic and sustainable advancement. This research asserts that the systemic incorporation of business ethics in Islamic banking systems jurisprudence is the primary underlying contributory factor for the socioeconomic advancement of Islamic banking institutions, while affording them a pronounced competitive prominence and articulating the primary underlying value proposition for Islamic economics systems’ jurisprudence.  This research has further continued the discourse on the impact of ethics to systems. Keyword : Islamic economic law, business ethics, Islamic jurisprudence, sustainable banking, Sharia governance, ethical ‍‌finance